Firm Dynamics and Job Creation in the Former Yugoslav Republic of Macedonia - World Bank (World Bank, Washington, DC, 2017)
Good jobs are in short supply in the former Yugoslav Republic of Macedonia. Sustainable, better employment opportunities must come from higher labor demand from a dynamic and internationally competitive private sector, the result of an advanced economic transition from a state controlled to a market led economy. This note focuses on job creation from the perspective of enterprise sector dynamics in the former Yugoslav Republic of Macedonia. The purpose is to understand, better, the dynamics of job creation, where and how firms and jobs are created, and the most important constraints to job creation from the firm perspective. Drawing on several sources of data, including firm registry, data on entrepreneurship, labor force surveys, and policy indicators, the note contributes to the job diagnostics necessary to devise relevant policy to increase job opportunities in the former Yugoslav Republic of Macedonia and is intended to provide guidance to researchers and policymakers in other countries wishing to understand better the role of the private sector in employment. Despite some significant business climate reforms, the former Yugoslav Republic of Macedonia has not seen private sector dynamics or ‘entrepreneurship’ improve sufficiently. In sum, the transition of workers and jobs from low productivity sectors to higher productivity sectors has stalled in the former Yugoslav Republic of Macedonia. Prior to the economic crisis, countries which had advanced more in the transition process saw higher productivity growth than the former Yugoslav Republic of Macedonia, more inflows of workers into the services sector, and substantive net job creation. In the former Yugoslav Republic of Macedonia, in contrast, labor reallocation is still incomplete. One fifth of the population remains in low productivity agriculture and one third is informally employed. Between 2007 and 2011 the formal private sector created only 12 percent of all new jobs.